Strategies for Teacher Education Programs to Support Indigenous Teacher Employment and Retention in Schools - Tessaro, Danielle; Landertinger, Laura; Restoule, Jean-Paul (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
This article seeks to contribute to the knowledge base regarding efforts to increase the supply of employed Indigenous teachers. In addition to supporting the learning and well-being of Indigenous students, increasing Indigenous teachers is critical for remote Indigenous communities with chronically understaffed schools. This study was conducted as a scoping review of 50 Teacher Education Programs (TEPs) across Canada, Australia, New Zealand, and the United States that have enacted efforts to increase Indigenous teachers. The study found a range of effective strategies, and this article will depict three strategies that can be enacted by TEPs to support Indigenous teacher graduates as they transition to employment. The strategies are: (1) creating employment opportunities, (2) identifying community needs and collaborating over practicum placements, and (3) providing ongoing support. The article concludes with a call for collaboration, funding, and data collection for the continued evaluation and improvement of strategies to increase Indigenous teachers.